2017
DOI: 10.1108/ijsms-05-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Variables affecting the market demand of sport lottery sales in China

Abstract: Today, sport betting is one of the fastest growing sectors in both of the gambling and sport industries globally. For instance, during the 2009-2010 fiscal year, the British gambling industry generated a gross income of £5.7 billion (Gambling Commission, 2010), where the sport betting sector had one of the largest market shares within the sports industry. Sport lottery plays a very important role in promoting the economic and social development, including providing employments, boosting consumer spending, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…As participants feel more satisfied with an organization's offerings, they will be more likely to be repeat customers and refer others to join (Eggert and Ulaga, 2002;Fornell et al, 1996;Maxham and Netemeyer, 2002;Zhou and Zhang, 2017). Zhang (2015) also recognized the importance of providing quality programs and the necessity of developing diversified programs in order to achieve market penetration and expansion by considering sociodemographic variables when planning marketing strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As participants feel more satisfied with an organization's offerings, they will be more likely to be repeat customers and refer others to join (Eggert and Ulaga, 2002;Fornell et al, 1996;Maxham and Netemeyer, 2002;Zhou and Zhang, 2017). Zhang (2015) also recognized the importance of providing quality programs and the necessity of developing diversified programs in order to achieve market penetration and expansion by considering sociodemographic variables when planning marketing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have indicated that in-depth analyses of market demand variables for a sport product(s) would enhance the understanding of consumer wants and accordingly allow managers to formulate a competitive strategy (e.g. Byon et al, 2010;Kim et al, 2009Kim et al, , 2013Min et al, 2015;Zhang et al, 1995;Zhou and Zhang, 2017).…”
Section: Theoretical Framework Market Demand Constructsmentioning
confidence: 99%
“…Certain authors have looked at it as a panacea for growth and development. Zhou and Zhang (2015) demonstrated that sports lottery promotes economic and social development through the provision of employment, boosting of consumer spending, generation of tax income, and promotion of various industries, such as communication, transport, manufacture, finance, and advertisement. Others researchers and groups have looked at it in a negative limelight associating sports betting to encouraging vices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the Public Services Index in the European Quality of Life Survey, the characteristics of Chinese community sports and relevant literature (e.g. Zhou and Zhang, 2017), this study identified five major components of community-sport services, including sport facility, sport organization, sport activity program, fitness test and sport instructor.…”
Section: Review Of Literaturementioning
confidence: 99%